2016
DOI: 10.2147/ott.s104729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evodiamine and berberine on miR-429 as an oncogene in human colorectal cancer

Abstract: Loss of epithelial organization and deregulated microRNAs are hallmarks of malignant carcinomas, but the relationship between them has been poorly understood. This study was designed to investigate the changes in the expression of E-cadherin, Par3, and miR-429 during the development of human colorectal cancer (CRC). E-cadherin and Par3 levels were quantitatively detected by immunohistochemistry and Western blotting. An in vitro culture of colorectal tissue was established to analyze the effect of berberine (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Colorectal cancer (CRC), which progresses from adenomas to adenocarcinomas, is a leading cause of cancer death worldwide [ 1 ]. It is widely accepted that this progression is triggered by the accumulation of both genetic and epigenetic factors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC), which progresses from adenomas to adenocarcinomas, is a leading cause of cancer death worldwide [ 1 ]. It is widely accepted that this progression is triggered by the accumulation of both genetic and epigenetic factors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Liu et al found that miR-429 was an oncogene regulated by evodiamine and berberine in human CRC. These studies indicated that miR-429 might play important roles during chemotherapy in CRC [ 28 ]. In our research, our novel results indicated that miR-429 was significantly correlated with 5-FU response in CRC patients, and exerted its important function in distinguishing the patients with a response to 5-FU treatment from the patients with no response.…”
Section: Discussionmentioning
confidence: 99%
“…86 In colon cancer cells, BBR down-regulated miR-429 and inhibited E-cadherin expression. 87 Together, BBR inhibits cancer invasion and metastasis by regulating the expression of microRNAs or interacting with them. Although studies have shown that BBR inhibited cancer development by interacting with microRNAs, the interaction sites and mechanisms associated with these inhibitory effects need to be further explored.…”
Section: Bbr's Other Functions Effects Of Bbr On Micrornamentioning
confidence: 99%